2010
DOI: 10.1590/s0034-89102010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Association of dental enamel lead levels with risk factors for environmental exposure

Abstract: Associação de níveis de chumbo no esmalte dentário com fatores de risco para exposição ambiental ABSTRACT OBJECTIVE:To analyze household risk factors associated with high lead levels in surface dental enamel. METHODS:A cross-sectional study was conducted with 160 Brazilian adolescents aged 14-18 years living in poor neighborhoods in the city of Bauru, southeastern Brazil, from August to December 2008. Body lead concentrations were assessed in surface dental enamel acid-etch microbiopsies. Dental enamel lead le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Graphite furnace atomic absorption Spectrophotometry (GFAAS) is a very attractive option for the determination of trace amount of lead in teeth [10,17,[31][32][33][34][35][36][37].…”
Section: Methods For the Determination Of Lead In Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphite furnace atomic absorption Spectrophotometry (GFAAS) is a very attractive option for the determination of trace amount of lead in teeth [10,17,[31][32][33][34][35][36][37].…”
Section: Methods For the Determination Of Lead In Teethmentioning
confidence: 99%
“…Several studies in humans have demonstrated that lead level in teeth has been used as an index of accumulation of lead and environmental pollution [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed a strong association between adolescents with high dental enamel lead levels living in or close a contaminated area [131]. In those three studies, the high lead levels seemed not affect the child population health.…”
Section: Grandjean Et Almentioning
confidence: 93%
“…In those three studies, the high lead levels seemed not affect the child population health. Another study showed a strong association between adolescents with high dental enamel lead levels living in or close a contaminated area [131]. Sakuma et al [130] reported that contamination from lead in a former mining area may explain the higher urinary arsenic values among the children living nearly, despite the median arsenic values do not warrant immediate health concern.…”
Section: Grandjean Et Almentioning
confidence: 99%
See 1 more Smart Citation